A global analysis of COVID-19 infection fatality rate and its associated factors during the Delta and Omicron variant periods: an ecological study - Thi Hong Nguyen, Nhi; Ou, Tsong-Yih; Huy, Le Duc; Shih, Chung-Liang; Chang, Yao-Mao; Phan, Thanh-Phuc; Huang, Chung-Chien (Frontiers in Public Health, 2023)
Background: The Omicron variant of SARS-CoV-2 is more highly infectious and transmissible than prior variants of concern. It was unclear which factors might have contributed to the alteration of COVID-19 cases and deaths during the Delta and Omicron variant periods. This study aimed to compare COVID-19 average weekly infection fatality rate (AWIFR); to investigate factors associated with COVID-19 AWIFR; and to explore the factors linked to the increase in COVID-19 AWIFR between two periods of Delta and Omicron variants. Material and methods: An ecological study has been conducted among 110 countries over the first twelve weeks during two periods of Delta and Omicron variant dominance using open publicly available datasets. Our analysis included 102 countries in Delta period and 107 countries in Omicron period. Linear mixed-effects models and linear regression models were used to explore factors associated with the variation of AWIFR over Delta and Omicron periods. Findings: During Delta period, the lower AWIFR were witnessed in countries with better government effectiveness index (β=-0.762, 95% CI (-1.238)-(-0.287)), and higher proportion of the people fully vaccinated (β=-0.385, 95% CI (-0.629)-(-0.141)). In contrast, higher burden of cardiovascular diseases was positively associated with AWIFR (β=0.517, 95% CI 0.102-0.932). Over Omicron period, while years lived with disability (YLDs) caused by metabolism disorders (β=0.843, 95% CI 0.486-1.2), proportion of the population aged over 65 (β=0.737, 95% CI 0.237-1.238) were positively associated with poorer AWIFR, high proportion of the population vaccinated with a booster dose (β=-0.321, 95% CI (-0.624)-(-0.018)) was linked with the better outcome. Over two periods of Delta and Omicron, the increase in government effectiveness index was associated with decrease of AWIFR (β= -0.438, 95% CI (-0.750)-(-0.126)); whereas higher death rates caused by diabetes and kidney (β=0.472, 95% CI 0.089-0.855) and percentage of population aged over 65 (β=0.407, 95% CI 0.013-0.802) were associated with a significant increase in AWIFR. Conclusions: The COVID-19 infection fatality rates was strongly linked withcoverage of vaccination rate, effectiveness of government, and health burden related to chronic diseases. Therefore, proper policies for improvement of vaccination coverage and support vulnerable groups could substantially mitigate the burden of COVID-19.